The Role of Oxytocin in Regulating Systemic Inflammatory Responses in Patients with Major Depressive Disorder - Mohammed, Asmaa Jamal (American Journal of Biomedicine and Pharmacy, 2026)
Background & Aims: MDD is known to be accompanied by a dysregulation of the neuroendocrine and immune system. Therefore, this study was performed to explore the connection between oxytocin and pro-inflammatory cytokines in subjects with chronic depression. Materials & Methods: A case-control study of 87 MDD patients case match with 87 healthy group was carried out at Azadi Teaching Hospital, Kirkuk, Iraq during February to June 2025). Serum content of oxytocin, cortisol, prolactin, IL‑6, TNF‑α, IL‑1β and IL‑10 was determined by ELISA. Severity of depression was evaluated using the HAM-D scale. Pearson correlation and ROC analyses were conducted. Results: MDD patients had significantly lower oxytocin (3.5 ± 1.2 vs. 5.2 ± 1.5 pg/mL, p < 0.001) and IL‑10 (2.6 ± 0.8 vs. 3.4 ± 1.0 pg/mL, p = 0.002), and higher cortisol (17.5 ± 5.0 vs. 13.2 ± 4.1 µg/dL, p < 0.001), prolactin (18.0 ± 6.1 vs. 13.5 ± 4.8 ng/mL, p = 0.001), IL‑6 (4.8 ± 1.6 vs. 2.1 ± 0.9 pg/mL, p < 0.001), TNF‑α (12.8 ± 4.3 vs. 8.5 ± 3.0 pg/mL, p < 0.001), and IL‑1β (3.2 ± 1.0 vs. 1.8 ± 0.7 pg/mL, p < 0.001) compared to controls. Patients showed moderate to severe HAM-D scores, confirming clinically significant depressive symptoms. Oxytocin correlated negatively with HAM-D scores (r = -0.53, p < 0.05) and pro-inflammatory cytokines. ROC analysis showed oxytocin (AUC = 0.82) and IL‑6 (AUC = 0.85) had the highest diagnostic accuracy. Conclusion: The study suggests downregulated oxytocin, up-regulated pro-inflammatory cytokines and HPA-axis activation in chronic depression. Oxytocin and IL‑6 could be used as potential biomarkers of MDD, reflecting neuroendocrine‑immune imbalance.